2020
DOI: 10.1039/d0na00311e
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial nanofibers outperform uniaxial nanofibers for the loading and release of pyrroloquinoline quinone (PQQ) for biomedical applications

Abstract: Pyrroloquinoline quinone (PQQ), present in breast milk and various foods, is highly recommended as an antioxidant, anti-inflammatory agent, and a cofactor in redox reactions in several biomedical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…In biomedical applications, coaxial nanofibers are superior to uniaxial nanofibers in terms of drug loading and releasing (165). The biggest characteristic of coreshell structure is that the release process of drugs can be better controlled to prevent drugs from being released prematurely, and the existence of core-shell structure can avoid the destruction of physical and chemical properties of drugs in the core layer by the external environment.…”
Section: Functional Applications Of Structural Electrospun Fibersmentioning
confidence: 99%
“…In biomedical applications, coaxial nanofibers are superior to uniaxial nanofibers in terms of drug loading and releasing (165). The biggest characteristic of coreshell structure is that the release process of drugs can be better controlled to prevent drugs from being released prematurely, and the existence of core-shell structure can avoid the destruction of physical and chemical properties of drugs in the core layer by the external environment.…”
Section: Functional Applications Of Structural Electrospun Fibersmentioning
confidence: 99%
“…The desired morphologies and structures of nanofibers can be achieved towards a diverse combination of complementary materials in the complicated core-shell composite structures fabricated via coaxial electrospinning [ 25 , 31 , 32 , 33 , 34 ]. Compared to uniaxial electrospinning in which a single needle is used, coaxial electrospinning requires two concentric needles with different polymer solutions to produce the core and shell of composite nanofibers [ 31 , 35 , 36 ]. Considerable efforts have been dedicated to the multifunctional properties and novelty of electrospun composite nanofibers which hold great potential for electronic devices, biomedicine, and tissue regeneration [ 35 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to uniaxial electrospinning in which a single needle is used, coaxial electrospinning requires two concentric needles with different polymer solutions to produce the core and shell of composite nanofibers [ 31 , 35 , 36 ]. Considerable efforts have been dedicated to the multifunctional properties and novelty of electrospun composite nanofibers which hold great potential for electronic devices, biomedicine, and tissue regeneration [ 35 , 37 , 38 , 39 , 40 , 41 ]. The superior combination of the complementary polymers in the core and shell structure is beneficial to the mechanical properties over the neat polymers [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coaxial electrospinning provides a strategy to fabricate core-shell structure nanofibers as a drug delivery system. It was reported that coaxial nanofibers exhibited lower release rates compared to that of uniaxial nanofibers, resulting in a prolonged release [156]. Recently, various drug delivery systems fabricated by coaxial electrospinning were reported.…”
Section: Drug Delivery Systemmentioning
confidence: 99%